Implementasi Metode Waterfall dalam Pengembangan Aplikasi Toko Online Bebasis Web di Cv Aishastore.Id - Rais Akbar Wibowo; Didik indrayana; Asriyanik Asriyanik (Syntax Corporation Indonesia, 2025)
This study aims to design and develop a web-based online store application for CV AishaStore.id, a small and medium enterprise specializing in selling herbal products. The application is designed using the Software Development Life Cycle (SDLC) with the Waterfall model, which includes phases such as requirements analysis, system design, application development, testing, and maintenance. Utilizing programming languages such as PHP, JavaScript, and CSS, along with MySQL as the database, the application offers key features including stock management, product catalog, transaction system, and user account management. Testing was conducted using the Black Box Testing method to ensure all features function according to user needs. The results of the study indicate that the application successfully improves operational efficiency by automating stock management, simplifying transaction recording, and providing a responsive and user-friendly shopping experience. Additionally, the application expands market reach and supports better decision-making through a structured system. This study is expected to serve as an effective solution for SMEs in addressing digital challenges, with further development potential such as integration with mobile platforms, advanced analytics features, and enhanced data security to broaden functionality and user convenience.